2009
DOI: 10.1111/j.1365-2184.2009.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of autologous mesenchymal stem cell injection in a large‐animal model of bilateral kidney ischaemia reperfusion injury

Abstract: In this unique autologous large-animal model, MSCs did not exhibit reparative or paracrine protective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 56 publications
(133 reference statements)
3
31
1
Order By: Relevance
“…The results obtained in this study contradict those in another report that showed the non-therapeutic effects of MSC transplantation in an ovine model of renal injury (37). Considering other reports, the mechanism by which cUCB-MSCs contribute to ameliorating renal failure in the present study could be related to the MSC secretome or prevention of progressive pathology or transdifferentiation of MSCs (38,39).…”
Section: Detection Of Transplanted Mesenchymal Stem Cells In the Kidncontrasting
confidence: 57%
“…The results obtained in this study contradict those in another report that showed the non-therapeutic effects of MSC transplantation in an ovine model of renal injury (37). Considering other reports, the mechanism by which cUCB-MSCs contribute to ameliorating renal failure in the present study could be related to the MSC secretome or prevention of progressive pathology or transdifferentiation of MSCs (38,39).…”
Section: Detection Of Transplanted Mesenchymal Stem Cells In the Kidncontrasting
confidence: 57%
“…In the cortex, MSCs were found in glomeruli and were rarely identified in the renal microvasculature. The MSC was not found in renal tubules (7).…”
Section: Discussionmentioning
confidence: 98%
“…Behr et al (2009) found that 60 min. bilateral ischemia induced mild renal injury with focal acute tubular necrosis; this pattern of lesions is closer to that observed in humans with ARF (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 gene transfer contributes to in vivo reendothelialization capacity of endothelial progenitor cells (28). However, some studies show that MSC could not exhibit reparative or paracrine protective properties (29). Confirmation of the exact effects of MSC on vascular injury is needed .…”
Section: Discussionmentioning
confidence: 99%